Effectiveness of a digital telemonitoring platform for cancer care of older patients: The ConnectElderlyPatientToDoctor study. Issue 3 (9th July 2022) - Rivière, Clémentine; Brureau, Laurent; Parnot, Charles; Becherirat, Selma; Duverger, Claire; Picchi, Hugo; Le Roy, Audrey; Vuagnat, Perrine; Schernberg, Antoine; Vanquaethem, Hélène; Helissey, Carole
Abstract: While telemedicine has been shown to improve the quality of care for cancer patients, it remains underused for older patients (OP), partly due to the assumption that OPs are unabled or unwilling to use digital tools. However, more than 50% of new cancers are diagnosed in people over 70. The ConnectElderlyPatientToDocto r study aimed to evaluate the OP compliance with the use of the digital telemonitoring platform Cureety in oncology. All cancer patients followed at the Military Hospital Bégin were eligible for the study. Patients were invited to respond to a symptomatology questionnaire personalized to their pathology and treatment. An algorithm evaluated the health status of the patient based on the reported adverse events. The population was divided into two groups, OP and younger patients (YP), based on a cut‐off at 70 years. The primary endpoint was to assess the compliance of OPs with the use of the digital oncology platform Cureety, compared to YP. From July 2020 to September 2021, a total of 117 patients were included in our study. We found that 66% of the patients were compliant, with no difference between the two groups (71.2% of YP, 61.7% of OP, P  = .29). In OPs, progression free survival (PFS) ratio at 6‐months was 64.6% in the tolerant patients vs 23.4% in the nontolerant patients (HR = 0.1980, 95% CI = 0.04431‐0.8845, P  = .0339). The median PFS was 23.3 months in the tolerant group vs 3.3 months in the nontolerant group ( P  = .0339). The data of overall survival are immature. OPs had a clear benefit from using this platform, similar to what was observed for YP. Patients felt less isolated and felt that they benefited from personalized care with early ambulatory medical care of adverse events. We also found that the health indicators collected with the platform in the first month of treatment are predictive of the progression of the disease. This solution makes it possible to streamline and improve the care pathway of OP. Abstract : What's new? Telemedicine has been shown to improve the quality of care for cancer patients. However, telemedicine remains underused for older patients, partly due to the assumption that they are unable or unwilling to use digital tools. Here, the authors demonstrate that telemonitoring is indeed accessible and beneficial to older patients. While using the platform, patients felt less isolated and that they benefited from personalized care. Moreover, the health indicators collected through the platform in the first month of treatment were predictive of disease progression. Telemedicine makes it possible to streamline and improve the care process of older cancer patients.